Efficacy of tranexamic acid in nasopharyngeal hemorrhage; single center prospective study and literature review - Septar Haldun; Andra-Iulia Suceveanu; Mihai Lupascu; Laura Mazilu; Alina Nicoara; Viorel Gherghina; Felix Voinea; Razvan Hainarosie; Alexandru Aristide Alexe; Ana Maria Dascalu; Adrian Paul Suceveanu (Journal of Mind and Medical Sciences)
Nasopharyngeal hemorrhage is one of the most common ear, nose, and throat (ENT) emergencies that present in a hospital or primary care clinic. While many cases of hemorrhage are self-limiting, in more severe cases medical intervention is necessary, either to cauterize the bleeding vessel or to pack the nose with various materials (thus involving specialized medical care and time, which implicitly lead to additional costs). In the case of the packaging, the medical treatment can in some cases be extremely painful and unpleasant. Tranexamic acid is an affordable, inexpensive, easy-to-use antifibrinolytic agent and with no notable side effects, as demonstrated by numerous studies related to most surgical fields. The aim of this paper is to provide an evidence-based approach to the use of tranexamic acid (TXA) in nasopharyngeal hemorrhages in our research center, comparing with the available literature on the subject, but presented in an updated form. As a conclusion, the combined use (intravenous and topical) of TXA may be a reasonable, safe and non-invasive option for hemodynamic stabilization of rhino-pharyngeal bleeding.